Regularities in the solar background magnetic field - Bumba, V. (Известия Крымской астрофизической обсерватории, 2009)
We are searching for the physical cause of regular long periods of solar activity recurrences and regularities in the background magnetic field distribution. We use the Stanford synoptic maps of the magnetic field and of the source surface magnetic field divided into different longitudinal zones. We demonstrate that the longitudinal background field concentrations and their longitudinal shift with time in the individual zones run parallel with lines connecting points of projections of meetings of some planetary pairs into the same maps. Further we show that very specific mutual positions of Jupiter and Saturn with respect to Venus and Earth during their oppositions and conjunctions principally differ during the phase of highest activity in the recent three odd cycles and two even cycles. Parallel with the sudden changes of the longitudinal field distribution, we again ascribe to Venus and Earth meetings, we characterize large-scale uni-polar magnetic structures, the development of which we also connect with these meetings. During the meetings, it is the positive polarity which predominates in the structures occupying the solar side facing the Earth, while the negative polarity is concentrated on the opposite side of the Sun. We suggest that another agent, possibly the magnetic and electric field acts parallel with the gravitational forces of the planetary system.